A 20-year experience in unilateral cleft lip repair: From Millard to the triple unilimb Z-plasty technique - Percy Rossell-Perry (Indian Journal of Plastic Surgery)
Background: This study describes a 20-year experience of treating patients with unilateral cleft lip. During this time, various techniques were used including Millard's technique and its modification and two types of geometrically designed procedures. The study objective was to compare surgical outcomes of different surgical techniques for unilateral cleft lip repair. Materials and Methods: This is a retrospective audit of outcomes after unilateral cleft lip repair performed by a single surgeon since 1995. Of the 827 patients who underwent surgery, 277 met the criterion of having anthropometric measurements performed ≥1 year postoperatively. The patients were stratified into three groups according to cleft severity: incomplete, complete with less deficiency (3–6 mm difference between cleft and non-cleft lip height) and complete with more deficiency (>6 mm difference between cleft and non-cleft lip height). Anthropometric measurements, scar assessment and complications were recorded. Results: There were no differences in outcomes between Millard and Reichert-Millard techniques for incomplete unilateral cleft lip. For complete unilateral cleft lip and less tissue deficiency, lip symmetry was better using upper rotation advancement plus double unilimb Z-plasty than the Reichert-Millard technique. For complete unilateral cleft lip and more tissue deficiency, lip symmetry was better after triple unilimb Z-plasty than after upper rotation advancement plus double unilimb Z-plasty. Conclusions: We presented a 20-year experience performing unilateral cleft lip repair. An individualised classification system with corresponding surgical techniques was successfully used during this period. The individualised surgical protocol used in this study allowed us to achieve improved surgical outcomes.